Sound Absorption Properties of Shredded Paper Wastes as Indoor Building Sound Absorber - Eun-Suk Jang; Hee-Jun Park (BioResources)
The sound absorption properties of shredded paper wastes (SPW) were evaluated. Two impedance tubes (large and small) were used to measure the sound absorption coefficient of different thicknesses of SPW sound-absorber (20, 40, 60, 80, and 100 mm). As the thickness of the SPW sound-absorber increased, the optimum sound absorption coefficient was shifted to a lower frequency direction. Based on the KS F 3503 (2002) standard, the sound absorption coefficients were 0.3 M for 20 mm, 0.5 M for 40 mm and 60 mm, and 0.7 M for both 80 mm and 100 mm. The sound absorption properties of this SPW showed comparable or better performance than other eco-friendly fibrous sound absorbers. SPW has not been previously considered for recycling applications. The findings imply that SPW has good sound absorption properties and can thus be employed as a cost-effective and environmentally friendly sound-absorbing material.